Konsep Tanggung Jawab dalam Aspek Hukum terhadap Kerugian yang Diderita Konsumen Akibat Penggunaan Produk yang Dipasarkan Perusahaan Retail - Pratama, Rizky Rahma; Apriani, Rani (Jurnal Ilmiah Wahana Pendidikan, 2025)
The rapid growth of the economic system in Indonesia also encourages increased business competition, including in the provision of basic goods for the community. The existence of retail companies that are now developing in various parts of Indonesia provides convenience for consumers to fulfill their daily needs without having to interact directly with producers. However, in this modern era, people are still faced with concerns regarding product safety that can endanger their safety. This research is a normative research with a statutory approach, which is based on the analysis of factual problems in the field. This study connects these realities with legal theories, legal concepts, and applicable regulations. As a provider of goods, retail companies have an obligation to ensure that the products sold are of good quality and safe for consumers. If defective products are found, expired, or contain hazardous materials that harm consumers, retail companies must be responsible in accordance with applicable legal provisions.